Strategi Manajemen Tata Kelola Lahan Pekarangan dalam Penanaman Tanaman Bawang Merah (allium ascalonicum) - Ruth Riah Ate; Tharmizi Hakim (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2023)
This article aims to analyze the internal factors and external factors that influence the strategy for developing management of shallot (allium ascalonicum) farming management in Minta Kasih Village, Salapian District, Langkat Regency. The problem is focused on how internal factors and external factors influence the management strategy of shallot farming management. In order to approach this problem, a theoretical reference from Management is used as art containing aesthetic meaning, beauty, harmonization, and making us more efficient for its users. Onion plants can be planted in the yard of the house to produce onions that can be used by the family. The data were collected through a survey and analyzed qualitatively. This study concludes that the internal factors of strength are natural resources, house yards, human resources, harvest season, group of mothers, and access to transportation. Internal factors of weakness are seeds, marketing, farmer partnerships, processing, and plant maintenance. External factors are opportunities, namely: the location of the cultivation yard, demand, farming profits and onion quality. External threat factors are: climate change, pests and diseases and prices.